Kepercayaan Diri dan Dukungan Sosial dengan Kemandirian pada Mahasiswa Perantauan - Annisa Wijayanti; Dian Kinayung (Empathy : Jurnal Fakultas Psikologi, 2022)
Self Confidence and Social Support with Independence for Overseas Students Self-confidence and social support with independence in overseas students. This study aims to examine the relationship between self-confidence and social support with independence in overseas students. The subjects in this study were 110 overseas students from the 2019 faculty of psychology, Ahmad Dahlan University. The research method used is quantitative method with measuring instruments used are independence scale, self-confidence scale, and social support scale. The data analysis used was multiple linear regression analysis technique using the Statistical Product and Service Solution (SPSS) 16.0 for windows computer program. The results of the major hypothesis obtained a regression value of R = 0.609 with p = 0.003 (p <0.05). This shows that there is a very significant relationship between the variables of self-confidence and social support with independence. The first minor result is r = 0.578 with p = 0.000 (p <0.01), meaning that there is a very significant positive relationship between self-confidence and independence. Furthermore, the second minor result is r = 0.062 with p = 0.473 (p <0.05), meaning that there is no relationship between social support and independence. Based on the results of this study, it can be concluded that the self-confidence variable provides an effective contribution of 35.08% to independence.